2017
DOI: 10.4315/0362-028x.jfp-16-451
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Nondesiccated and Desiccated Cronobacter sakazakii in Reconstituted Infant Formula by Combination of Citral and Mild Heat

Abstract: The objective of this study was to evaluate the combined effect of citral plus mild heat on nondesiccated and desiccated Cronobacter sakazakii in reconstituted infant formula. Various concentrations of citral (0, 0.3, 0.6, and 0.9%) combined with various temperatures (25, 45, 50, and 55°C) were applied to nondesiccated and desiccated cocktails of three C. sakazakii strains (approximately 6.0 log CFU mL) in reconstituted infant formula, and the bacterial populations were assayed periodically. The combined treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The vacuum packaging had the greatest impact on reducing the stress resistance of C. sakazakii , whereas desiccation without 10-day storage had the least impact. Our previous study demonstrated that desiccation stress significantly decreased the heat resistance of C. sakazakii in reconstituted infant formula (Shi et al, 2017). On the contrary, Chen and Jiang (2017) found that desiccated Salmonella cells in poultry litter showed enhanced heat resistance as compared to non-desiccated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vacuum packaging had the greatest impact on reducing the stress resistance of C. sakazakii , whereas desiccation without 10-day storage had the least impact. Our previous study demonstrated that desiccation stress significantly decreased the heat resistance of C. sakazakii in reconstituted infant formula (Shi et al, 2017). On the contrary, Chen and Jiang (2017) found that desiccated Salmonella cells in poultry litter showed enhanced heat resistance as compared to non-desiccated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other members of the Enterobacteriaceae family, C. sakazakii is reported to be significantly more thermotolerant (Amalaradjou and Venkitanarayanan, 2011). This feature represents a competitive advantage, facilitating its survival during improper PIF reconstitution (Shi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most in vitro antimicrobial activity assays are performed with microorganisms grown under optimal laboratory conditions (Shi et al 2017), which further needs their evaluation in real food system as different components of food may interact and affect the biological activities of test compounds. Another important factor likely to affect in situ efficacy of antimicrobial compound is the physiological state of target organism as food borne pathogens are exposed to a myriad of stresses during processing (Bouarab Chibane et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to ensure microbial safety, FAO/ WHO (2006) and WHO (2007) recommended reconstitution of PIF with water that is no cooler than 70°C. However, thermal processing during manufacturing and use of hot water (~70°C) for reconstitution may deteriorate the organoleptic and nutritional properties of PIF (Agostini et al 2004;Shi et al 2015Shi et al , 2017. Moreover, parents and caregivers do not strictly adhere to recommended guidelines, leading to reconstitution of PIF at a temperature which might favour the growth of Cronobacter (Chap et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition TQ is found as an antibacterial resistance modifier [8], while synergistic to particular antibiotic agents [3,6,7]. According to Shi et al TQ significantly reduced the growth of Cronobacter sakazakii with the higher concentration (30 µM) and temperature (55 °C) applied [9]. The fungal species Candida albicans, C. krusei, C. tropicalis, Epidermophyton floccosum, Microsporum canis, M. gypseum, Trichophyton interdigitale, T. mentagrophytes and T. rubrum were found to be susceptible to TQ [10,11].…”
Section: Antimicrobial Activities Of Tqmentioning
confidence: 99%